Verso la neutralità climatica di architetture e città green Sperimentazioni e casi di studio nel Nord e Mittel Europa - Tucci, Fabrizio (Architettura e Innovazione. Built Environment Technologies and Healthy Architectures, 2023)
Among the experiments on the quality of living in urban spaces, those aimed at increasing the capacity to adapt and mitigate climate change are of fundamental importance, as they contribute, with adequate measures, to the decarbonization processes and the achievement of full climate neutrality. Faced with climate change, the increase in risks and vulnerabilities to their impacts, the persistence of climate-altering emissions, the growing European energy crisis, important actions by cities are necessary and urgent to become more resilient, responsible, and pro-active in reacting to the sudden and increasingly less controllable transformations resulting from environmental, economic, and social changes. Adaptation and mitigation measures to keep global temperatures within 1.5°C could avoid some of the most devastating impacts of ongoing climate change, but their implementation is well behind the 2015 roadmap : if average temperatures were to reach an increase of 2°C, the ecosystems currently considered vulnerable would significantly increase the probability of extinction, increasing it exponentially with a reaching of 3°C. A serious decarbonization operation of cities and urban districts therefore becomes of fundamental importance. This book shows the results of design experiments, carried out or underway in Northern and Central Europe, deriving from two major research projects carried out, one at a national level (PRIN), the other within a European framework (Green City Network) on projects of urban districts and eco-districts, with a final selection of over forty case studies in Northern and Central Europe, which work on the systematization of the six strategic axes that mark the path towards climate neutrality: energy transition, bioclimatic effectiveness, circularity of resources, functional mix, sustainable mobility, and green and gray CO2 subtraction. Axes that are followed with a planning perspective through the improvements achieved in terms of decarbonization in the context of the adoption of the technological-environmental solutions found, with the aim of defining new inter-scalar, multidisciplinary, responsible, and sustainable development protocols.